Current Research on MoS2-Based Heterojunction Photocatalysts for Persistent Organic Pollutants Degradation - Isac Luminita; Cazan Cristina (MDPI, 2025)
Currently, continuous population growth and unsustainable industrialization have caused ongoing water pollution, with harmful consequences for human health and the environment. Persistent organic pollutants (dyes, active pharmaceutical compounds, pesticides, etc.) are discharged into water from various industrial, agricultural, and domestic activities. Therefore, wastewater treatment through sustainable technologies is imperative, representing a great and real challenge for worldwide research. Photocatalysis, an innovative and green technology, uses advanced oxidation processes in the presence of a photocatalyst, usually a semiconductor with expanded light absorption ability and high conductivity for photogenerated charge carriers. Molybdenum disulfide (MoS2) is an n-type semiconductor with different morphologies, variable bandgap energies (Eg = 1.1-2.63 eV), and numerous applications. Although pristine MoS2 exhibits special structural and optoelectronic properties, its photocatalytic activity can be further improved through various strategies, and constructions with the heterojunctions construction with other semiconductors being frequently pursued. This review extensively studies the recent research (the last 4 years) on MoS2 and MoS2-based heterojunction (I-type, II-type, Z-scheme, S-scheme) photocatalysts for degrading organic contaminants under simulated and sunlight irradiation in wastewater treatment. Even if in a relatively short time (a few years) valuable studies have been reported on this topic, there are still numerous challenges facing future research.